Peningkatan Pemahaman Petani Terhadap Fungsi Akar Dan Daun Pada Kelompok Tani Desa Sekincau Lampung Barat - Eko Pramono; Tundjung Tripeni Handayani; Sri Wahyuningsih (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Sekincau Village is a hilly area with soil conditions that are favorable for horticultural crop cultivation, including vegetables. The farmers in Sekincau Village generally have a good understanding and mastery of horticultural cultivation techniques, but they lack adequate knowledge about the roles and functions of plant organs, especially the root and leaf organs, which are crucial for plant growth and development. The problem is how to help the farmers in Sekincau Village gain knowledge about the roles and functions of plant root and leaf organs. The purpose of this community service activity is to provide knowledge to the farmers in Sekincau Village about the roles and functions of plant root and leaf organs. To achieve this goal, training on observing and explaining the functions of plant root and leaf organs was conducted using the lecture method. It is hoped that the farmers will not only understand the importance of plant care from seed, fertilization, to harvest age with proper treatment and maintenance, but also realize the importance of the functions of root and leaf organs, which will ultimately affect increased productivity and improve agricultural income. Based on the training conducted, there was an increase in the participants' knowledge and understanding regarding the important roles of root and leaf functions in improving plant productivity. The average increase in participants' knowledge was 33.1 points. The hope for the future is that the knowledge and understanding gained will not only improve, but also be applied in planting and maintaining crops to achieve optimal productivity results.